2000
DOI: 10.1046/j.1365-2265.2000.00946.x
|View full text |Cite
|
Sign up to set email alerts
|

Raised plasminogen activator inhibitor‐1 (PAI‐1) is not an independent risk factor in the polycystic ovary syndrome (PCOS)

Abstract: Plasminogen activator inhibitor-1 activity is not raised in women with PCOS independent of obesity and these results do not support the hypothesis that it may contribute to their anovulatory infertility, or increase their risk of thrombosis. The only significant metabolic features of the PCOS independent of obesity are insulin resistance, hyperinsulinaemia and lower HDL/total cholesterol ratio. The higher frequency of a positive family history of thrombosis in these women nevertheless requires further explanat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 16 publications
(14 reference statements)
0
33
0
1
Order By: Relevance
“…14 While some studies have found PCOS to be associated with coronary heart disease risk factors, [15][16][17][18][19][20] other studies have shown that women with PCOS were 3 times more likely to have a family history of venous thrombosis. 21 Mak and Dokras 22 hypothesized that women with PCOS likely have an increased baseline risk for developing thrombosis compared with other women in the general population. However, no study has evaluated the prevalence of VTE among women with PCOS compared with women without PCOS.…”
Section: Author Manuscript Author Manuscriptmentioning
confidence: 99%
“…14 While some studies have found PCOS to be associated with coronary heart disease risk factors, [15][16][17][18][19][20] other studies have shown that women with PCOS were 3 times more likely to have a family history of venous thrombosis. 21 Mak and Dokras 22 hypothesized that women with PCOS likely have an increased baseline risk for developing thrombosis compared with other women in the general population. However, no study has evaluated the prevalence of VTE among women with PCOS compared with women without PCOS.…”
Section: Author Manuscript Author Manuscriptmentioning
confidence: 99%
“…It has been demonstrated that insulin resistance correlates positively with plasma PAI-1 levels (21). Hyperinsulinemia, when present in PCOS, may further increase PAI-1 levels, especially when it acts on the genetic background of homozygosity like 4G/4G.…”
Section: Genotype Subgroups Controlsmentioning
confidence: 99%
“…These findings might elucidate some discrepancies regarding fibrinolytic activity in PCOS, as earlier studies indicate both increased PAI-1 activity [15,100,101,160] and normal PAI-1 activity in PCOS patients [102,103] [159]. Thus, it is plausible studies indicating no difference in PAI-1 activity have included a more heterogeneous population of PCOS patients with regard to hyperandrogenism.…”
mentioning
confidence: 74%
“…Increased mass concentration of tPA, as a marker of endothelial disturbances, is possibly a better predictor for coronary heart mortality [98] than PAI-1 activity and is specifically associated with myocardial infarction in young women [99]. The triad obesity, raised triglycerides and, raised insulin levels is the most consistent predictor of impaired fibrinolysis and is often found in PCOS women [15,[100][101][102][103]. Earlier studies on PCOS women suggest both increased and normal levels of PAI-1 activity [15,[100][101][102][103], while studies on tPA-mass in PCOS patients are less ambiguous with increased levels [104][105][106], although at least one study reported unchanged levels [107].…”
Section: Fibrinolysismentioning
confidence: 99%
See 1 more Smart Citation